Ruang Sebagai Wahana Makna: Aspek Simbolik Pola Tata Ruang dalam Rekayasa Pemukiman Kuna di Maluku - Marlon NR Ririmasse (Balai Arkeologi Maluku, 2007)
The study of the spatial patterns believed as a key to study the culture of the past communities. A model that used by a community to construct their settlement, is also believed had been created according to their cultural principal. This is why the settlement pattern always been seen as a symbolic media to represent these principal. This article tries to discuss how ancient Mollucas spatial perspective in created their settlement.